SCALAR IMPLICATURE IN FACEBOOK - Lakamau, Feronika (LINGUISTIK TERAPAN, 2023)
This research explores the phenomenon of scalar implicature in Facebook status updates, using Yule's systems theory to dissect the implied meanings conveyed through scalar expressions. The research reveals that scalar implicature significantly influences communication on Facebook, providing more insight into the construction of implicatures. Noteworthy findings include examples of scalar implicature in status updates featuring terms such as "some", "few", "more", "more", "many", "all", "most", and "none". This research aims to find out how these scalar terms are used by Facebook users to communicate nuanced messages behind the explicit substance of the status,  underscore the importance of understanding the interaction between scalar terms, pragmatic elements, and semantic components for effective communication on platforms such as Facebook. Using a qualitative descriptive approach, the research examined data drawn from Facebook status updates to underscore the intricate relationship between scalar expressions and pragmatic and semantic elements in communication. The listening method combined with reading, selecting, and note-taking techniques produced the data. Statements, details, and proverbs that appear in the status updates of the author's Facebook page This study underscores how users use scalar terms to effectively communicate nuanced meanings and intentions on social media platforms such as Facebook. By emphasizing the importance of understanding scalar implicatures in achieving communication goals, this study highlights the use of language in everyday online interactions. The implications of this study extend to a broader understanding of language use in social media settings, emphasizing the critical role of scalar implicatures in facilitating effective communication.